Pengaruh Kekasaran Permukaan Terhadap Ketebalan Lapisan Hasil Hot Dipped Galvanizing (HDG) - Alamsyah, Fikrul Akbar; Setyarini, Putu Hadi; MF, Femiana Gapsari (Jurnal Rekayasa Mesin, 2012)
The process of Hot Dipped Galvanizing (HDG) is done in this study in order to cover steel AISI 1010. This study is aimed at investigating the influence of the variation of roughness level of specimen towards the layer thickness of the hot dipped galvanizing of steel AISI 1010. The level of roughness of the specimen is obtained from grinding on grid 100, 500, 800, and 1000. This process causes difference in the roughness of the surface which is measured by using the Surface Roughness Test. The controlled variable is dipping temperature of 480oC. The time of hot dipped galvanizing is 6 minutes, while the time of grinding is 3 minutes. The test done in this study is non destructive test with spray test. The result showed that the layer thickness increased as the function of the roughness.Keywords: hot dipped galvanizing, spray test, layer thickness surface roughness.